Symptoms of Temporomandibular Disorders in the Population: An Epidemiological Study - de Godoi Goncalves, Daniela Aparecida [UNESP]; Dal Fabbro, Amaury Lelis; Duarte Bonini Campos, Juliana Alvares [UNESP]; Bigal, Marcelo E.; Speciali, Jose Geraldo (Quintessence Publishing Co Inc, 2010)
Aims: To estimate the prevalence of symptoms of temporomandibular disorders (TMD) as a function of age and gender, in a representative urban sample from the Brazilian population. Methods: A total of 1,230 inhabitants (51.5% women) aged 15 to 65 years were interviewed by a validated phone survey. Sample size had been previously calculated. TMD symptoms were assessed through five questions, as recommended by the American Academy of Orofacial Pain, in an attempt to identify possible TMD. Data were derived by age and gender. Prevalence of each TMD symptom, and of combination of symptoms, was calculated. Results: At least one TMD symptom was reported by 39.2% of the individuals. Pain related to TMD was noted by 25.6% of the population. Temporomandibular joint (TMJ) sound was the most common symptom of TMD, followed by TMJ pain and masticatory muscle pain. All symptoms were more prevalent in women than in men. With men used as the reference, a relative risk (RR) of at least one TMD symptom in women was 1.31 (95% confidence interval [CI] = 1.14 to 1.52). When at least two symptoms were present, the RR was 1.93 (95% CI = 1.49 to 2.51). For three or more TMD symptoms, the RR was 2.49 (95% CI = 1.67 to 3.71). Women were also more likely than men to have TMD pain (RR = 1.78; 9% CI = 1.45 to 2.18). Conclusion: Individual symptoms, as well as a combination of TMD symptoms, are prevalent in the Brazilian urban population and are more frequent in women than in men. Additional studies should focus on risk factors for and relevance of TMD for the sufferers. J OROFAC PAIN 2010;24:270-278
Keywords: epidemiology; facial pain; prevalence; temporomandibular joint